2019
DOI: 10.1002/ange.201906031
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Complexities of Pseudocontact Shift Analysis in Lanthanide Coordination Complexes of Differing Symmetry

Abstract: In two closely related series of eight-coordinate lanthanide complexes,aswitch in the sign of the dominant ligand field parameter and striking variations in the sign, amplitude and orientation of the main component of the magnetic susceptibility tensor as the Ln 3+ ion is permuted conspire to mask modest changes in NMR paramagnetic shifts, but are evident in Yb EPR and Eu emission spectra.Lanthanide induced shift and paramagnetic relaxation enhancement are subjects of continuous research driven by new applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The variation of overall ligand polarizability and its directionality, involving the electrostatic interaction between induced dipoles on the ligand and the quadrupole moment on the Ln 3+ ion, is important in determining the “allowedness” of f–f electronic transitions. , Thus, it is the overall ligand molecular polarizability that is important in determining the ligand field. Other examples of switches in the sign of B 0 2 can be identified when complex constitution and local symmetry vary. The difference between the emission spectra of [EuL 8b ] and [EuL 9 ] + (Figure ) is consistent with a change in sign, as symmetry changes from C 1 to C 2 . , Other cases have been reported, including systems involving reversible coordination of a polarizable N atom, which following protonation is replaced by water. …”
Section: Overview Of Factors Determining Ligand Field Splittingsupporting
confidence: 73%
See 3 more Smart Citations
“…The variation of overall ligand polarizability and its directionality, involving the electrostatic interaction between induced dipoles on the ligand and the quadrupole moment on the Ln 3+ ion, is important in determining the “allowedness” of f–f electronic transitions. , Thus, it is the overall ligand molecular polarizability that is important in determining the ligand field. Other examples of switches in the sign of B 0 2 can be identified when complex constitution and local symmetry vary. The difference between the emission spectra of [EuL 8b ] and [EuL 9 ] + (Figure ) is consistent with a change in sign, as symmetry changes from C 1 to C 2 . , Other cases have been reported, including systems involving reversible coordination of a polarizable N atom, which following protonation is replaced by water. …”
Section: Overview Of Factors Determining Ligand Field Splittingsupporting
confidence: 73%
“…The difference between the emission spectra of [EuL 8b ] and [EuL 9 ] + (Figure 2) is consistent with a change in sign, as symmetry changes from C 1 to C 2 . 3,14 Other cases have been reported, including systems involving reversible coordination of a polarizable N atom, which following protonation is replaced by water. 49−51…”
Section: Variation Of Complex Constitution and Symmetrymentioning
confidence: 99%
See 2 more Smart Citations
“…".Using a rigid framework as e.g. DOTA-derived chelators, the lanthanide ion can be conveniently accommodated in the cavity and the tightly chelating ligand ensures chemical stability and inertness towards the environment of the LCT, which is a unique feature that clearly supersedes the stability of open-chain chelator-based LCTs[9].The investigation of the intrinsic anisotropies of lanthanide complexes in combination with their structural properties is subject of current research[52,53,158,159]. Furthermore, Mironov et al reported quantitative relations between ligand atom positions and geometries and the observed anisotropies[144].…”
mentioning
confidence: 99%